Comparative Evaluation of Shear Bond Strength of Luting Cements to Different Core Buildup Materials in Lactic Acid Buffer Solution - Patil, Siddharam M. (J Clin Diagn Res, 2015)
AIM AND OBJECTIVES: The core buildup material is used to restore badly broken down tooth to provide better retention for fixed restorations. The shear bond strength of a luting agent to core buildup is one of the crucial factors in the success of the cast restoration. The aim of this invitro study was to evaluate and compare the shear bond strength of luting cements with different core buildup materials in lactic acid buffer solution. MATERIALS AND METHODS: Two luting cements {Traditional Glass Ionomer luting cement (GIC) and Resin Modified Glass Ionomer luting cement (RMGIC)} and five core buildup materials {Silver Amalgam, Glass ionomer (GI), Glass Ionomer Silver Reinforced (GI Silver reinforced), Composite Resin and Resin Modified Glass Ionomer(RMGIC)} were selected for this study. Total 100 specimens were prepared with 20 specimens for each core buildup material using a stainless steel split metal die. Out of these 20 specimens, 10 specimens were bonded with each luting cement. All the bonded specimens were stored at 37(0)c in a 0.01M lactic acid buffer solution at a pH of 4 for 7days. Shear bond strength was determined using a Universal Testing Machine at a cross head speed of 0.5mm/min. The peak load at fracture was recorded and shear bond strength was calculated. The data was statistically analysed using Two-way ANOVA followed by HOLM-SIDAK method for pair wise comparison at significance level of p<0.05. RESULTS: Two-Way ANOVA showed significant differences in bond strength of the luting cements (p<0.05) and core materials (p<0.05) and the interactions (p<0.05). Pairwise comparison of luting cements by HOLM-SIDAK test, showed that the RMGIC luting cement had higher shear bond strength values than Traditional GIC luting cement for all the core buildup materials. RMGIC core material showed higher bond strength values followed by Composite resin, GI silver reinforced, GI and silver amalgam core materials for both the luting agents. CONCLUSION: Shear bond strength of RMGIC luting cement was significantly higher than traditional GIC luting cement for all core buildup materials except, for silver amalgam core buildup material. RMGIC core material showed highest shear bond strength values followed by Composite resin, GI Silver Reinforced, GI and Silver Amalgam core materials irrespective of luting cements.